Community nurses’ perspectives on a novel blended training approach: a qualitative study - Chou Chuen Yu (BMC Nursing, 2022)
Abstract Background Transiting into the community setting often presents novel difficulties for nurses because the role demands skills that might not have been obtained through usual clinical experience or training. The Ageing-in-Place Community Care Team (AIP-CCT) Community Nurse Basic Training programme was developed to address this learning gap. This training programme prepares nurses to lead in a multi-disciplinary team in delivering patient-centred care to patients with progressive or life-limiting conditions in the community setting. This study evaluated the inaugural training programme provided to a group of nurses from an acute hospital in Singapore. Methods Qualitative in-depth interviews were carried out with 13 participants from the training programme three-months after completion of the AIP-CCT Community Nurse Basic Training programme provided by an acute hospital to understand the programme’s impact on their knowledge, skills and clinical practice, as well as barriers and facilitators to learning. Results Overall, perception towards the training course was mixed. Course content was found to be relevant, and participants reported that training led to improvement in their practice. However, experienced nurses felt that the content of some modules were lacking in depth. This could have explained why only junior nurses tended to hold favourable attitudes and felt that the training led to increase in their confidence level. Although medical content was assessed favourably, the course was not able to address some of the constraints faced by community nurses such as managing expectations and handling difficult patients in the home care setting. For some modules, face-to-face training was preferred and e-learning components can be improved to increase communication and interaction. Conclusion This study provided insights into how a community nurse training programme could be developed to meet the needs of community nurses. The training was able to reinforce skills and knowledge, address knowledge gaps and provide new clinical care approaches and communication strategies. These incremental effects on experienced community nurses could be extrapolated to have greater benefits for inexperienced community nurses. Based on findings of the study, potential changes to the training programme were discussed to improve training outcomes.